Managing Mergers Across Borders: A Two-Nation Exploration of a Nationally Bound Administrative Heritage - Lubatkin, Michael; Calori, Roland; Very, Philippe; Veiga, John F. (Organization Science, 1998)
Top managers of British and French firms, which were recently acquired by either British or French firms, were surveyed as to their perceptions of the administrative approach—reflected in integrating mechanisms—used by the acquiring firms to establish headquarters-subsidiary control. Four types of integrative mechanisms were examined: structural, systems, social, and managerial. A multiple analysis of covariance model, coupled with a two-nation (British and French), two-merger type (domestic, cross-national) sampling design, found evidence that the administrative approaches used by managers during merger integration from two nations partially reflect their different heritages, and that these differences are consistent with national differences and the theoretical perspectives of institutional development and cross-cultural studies. Our findings, while exploratory, provide insight into the administrative difficulties of managing across borders and help us understand why many cross-national firms continue to use ethnocentric approaches in spite of the incentives for adopting a transnational approach. Moreover, our findings add one more voice to a growing chorus calling for a theory of the firm, as embedded, institutionally, culturally, and historically.